Effect of concomitant use of pitavastatin with neoadjuvant chemotherapy protocols in breast cancer patients: A randomized controlled clinical trial - Samar A. Dewidar; Omar Hamdy; Ahmed Eltantawy; Mohamed El-Mesery; Amal M. El Gayar; Moetaza M. Soliman (Elsevier, 2022)
Introduction: Preclinical studies have demonstrated the possible anticancer effects of statins, but the synergistic effect of concomitant statin use with standard chemotherapy protocols in patients with breast cancer has not yet been investigated. Aim: The current study aimed to evaluate the efficacy of concomitant pitavastatin use with neoadjuvant chemotherapy protocols in patients with breast cancer. Methods: This study was a randomized controlled clinical trial. A total of 70 adult female patients with pathologically-proven invasive breast cancer were randomized to receive or not receive pitavastatin (2 mg) oral tablets once daily concomitantly with standard neoadjuvant chemotherapy protocols for 6 months. The primary outcomes of this study were changes in tumor size and changes to the Ki67 index. In addition, secondary outcomes were changes in cyclin D1 and cleaved caspase-3 serum levels. This study was registered at ClinicalTrials.gov (Identifier: NCT04705909). Results: Patients in the pitavastatin group showed significantly higher median (IQR) reductions in tumor size [−19.8 (−41.5, 9.5)] compared to those in the control group [−5.0 (−15.5, 0.0), p = 0.0009]. The change in Ki67 from baseline to the end of therapy was similar between the two groups (p = 0.12). By the end of therapy, the cyclin D1 levels in the pitavastatin group were significantly decreased [median (IQR) change of − 10.0 (−20.2, −2.9) from baseline], whereas the control group showed an increase in cyclin D1 levels [14.8 (4.1, 56.4)]. The median (IQR) caspase−3 was elevated in the pitavastatin group 1.6 (0.2, 2.2), and decreased in the control group (−0.2 (−1.1, 0.0), p = 0.0002).Subgroup analysis of the pitavastatin group revealed that patients with positive human epidermal growth receptor 2 (HER2) had higher median (IQR) reductions in Ki67 [−35.0 (−70.0, −12.5)] than those with negative HER2 [2.5 (−15.0, 10.0), p = 0.04]. All patients who achieved a complete pathological response (n = 9) exhibited an HER2-neu positive receptor at baseline. Conclusion: Concomitant use of pitavastatin with standard neoadjuvant chemotherapy protocols may improve neoadjuvant chemotherapy responses in patients with breast cancer.